HUBUNGAN TINGKAT STRES DENGAN POLA SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMPN 17 MALANG: HUBUNGAN TINGKAT STRES DENGAN POLA SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMPN 17 MALANG - Sherly Ignasia; Anik Purwati; Rani Safitri (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: This study aims to investigate the relationship between stress levels and menstrual cycle patterns in adolescent girls at SMPN 17 Malang. Mental and reproductive health are two important aspects of adolescent life, and this research tries to understand the interaction between the two. Methods: This study employed a cross-sectional approach and a quantitative research design. We collected data from a total of 48 female teenagers at SMPN 17 Malang. We used simple random sampling as the sampling method. We measured stress levels using a standardised, tested questionnaire, and monitored menstrual cycle patterns through daily records reported by respondents. Results: Data analysis shows that the majority of adolescent girls experience moderate levels of stress (72.9%), while 50% of them have regular menstrual cycles. However, the Chi-Square statistical test showed that there was no significant relationship between stress levels and menstrual cycle patterns at SMPN 17 Malang (p > 0.05). Conclusion: Although there are variations in stress levels and menstrual cycle patterns, this study did not find a significant relationship between these two variables at SMPN 17 Malang. These results provide valuable insight into the mental and reproductive health conditions of adolescent girls in the school environment. We need further research to understand other factors that may influence the relationship between stress and menstrual cycle patterns in adolescent girls. Keywords: Young Women, Menstrual Cycle, Stress.